2012
DOI: 10.1188/12.cjon.372-377
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Support and Resource Needs Among African American Older Adults

Abstract: Older African Americans face substantial barriers to state-of-the-art cancer care. Implementing culturally appropriate support throughout cancer therapy is critical to improving cancer outcomes and quality of life for this vulnerable population. The purpose of this study was to obtain experiential data regarding cancer diagnosis and treatment, and analyze survivors’ recommendations regarding treatment-related needs, psychosocial support, and strategies and resources. Four main issues emerged from the study: (a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…At least two coders reviewed each transcript, using a previously described inductive approach to coding [27]. The team developed all concepts and themes, based on the final codes.…”
Section: Methodsmentioning
confidence: 99%
“…At least two coders reviewed each transcript, using a previously described inductive approach to coding [27]. The team developed all concepts and themes, based on the final codes.…”
Section: Methodsmentioning
confidence: 99%
“…Aging cancer survivors must deal with consequences of cancer and related therapies that may overlap with simultaneous effects of other chronic conditions or life changes that can serve as barriers to a return to normalcy. Oncology nurses should be attentive to the specific needs of older adult cancer survivors, particularly as they relate to setting goals, planning for the future, physical and social functioning, cancer- and non–cancer-related symptoms, engagement in valued activities, and ability to maintain independence (Bellury et al, 2013; Deimling, Sterns, Bowman, & Kahana, 2007; Lyons, Erickson, & Hegel, 2012; Wenzel, Jones, Klimmek, Krumm, et al, 2012). Older adult survivors seeking to reestablish a sense of normalcy may benefit from education and assistance distinguishing normal, aging-related changes from pathologic changes from cancer, other illnesses, or possible late effects of cancer therapies.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis reported in the current article was embedded within a larger randomized, controlled trial of a nurse-led supportive intervention for rural-dwelling cancer survivors and the people who support them (Wenzel, Jones, Klimmek, Krumm, et al, 2012; Wenzel, Jones, Klimmek, Szanton, & Krumm, 2012). The research reported in the current article used an intensive, multiple case study design (Stake, 1995) and grounded theory analysis techniques (Charmaz, 2006) to evaluate the fit between existing theoretical knowledge related to the process of managing recovery and to generate new theoretical knowledge about that process.…”
Section: Methodologic Approachmentioning
confidence: 99%
“…Rural cancer survivors may also be disproportionately burdened by treatment-related costs given their geographic isolation, socioeconomic disparities, and limited access to care. In qualitative studies, financial hardship is a common theme among rural cancer survivors (2)(3)(4)(5). In addition, Pisu and colleagues found that, among rural breast cancer survivors, out-of-pocket (OOP) costs represented approximately 10% of available income, with substantially higher OOP cost to income burdens observed for rural, low-income survivors (6).…”
Section: Introductionmentioning
confidence: 99%